Blood autoantibodies against tumor-associated antigens as biomarkers in early detection of colorectal cancer - Chen, Hongda; Werner, Simone; Tao, Sha; Zörnig, Inka; Brenner, Hermann (Cancer letters, 2014)
Multiple studies have shown that cancer patients produce detectable autoantibodies against certain tumor-associated antigens, which might be promising blood biomarkers for early detection of colorectal cancer (CRC). We aimed to provide an overview of published studies on blood autoantibody markers for early detection of CRC and to summarize their diagnostic performance. A systematic literature search was performed in PubMed, ISI Web of Knowledge and EMBASE to find relevant studies published until 23 July 2013. Relevant information, such as study population characteristics, autoantibodies studied, analytical methods and diagnostic performance characteristics was independently extracted by two reviewers. Overall, 67 studies evaluating 109 autoantibody markers were included. Most individual markers showed low sensitivity (below 25%) for detecting CRC, along with high specificity close to 100%. Occasionally reported higher sensitivities for specific antibodies are yet to be replicated in independent studies. Generally, more promising results were seen for combinations of multiple autoantibody markers. But again, these promising results are yet to be replicated in other samples. In conclusion, autoantibody signatures may become a promising approach to noninvasive CRC screening. Optimized marker panels are yet to be developed, and promising results require validation in large screening populations.
Gesehen am 11.09.2020